Automating sentinel-1 SLC product processing: Parallelization and optimization for efficient polarimetric parameter extraction - Hansanee Fernando; Kwabena Nketia; Thuan Ha; Sarah van Steenbergen; Heather McNairn; Steve Shirtliffe (MethodsX, 2025)
Processing Sentinel-1 (S1) Single Look Complex (SLC) data is time-consuming, even with software like SNAP or PolSARpro. Command line processing on Windows provides an automated alternative, enabling R-based processing of multiple S1-SLC files without manual interaction. Here we demonstrate a user friendly automated process, to process an unlimited number of S1-SLC images, tailored for users with minimal SAR or programming competence. The proposed workflow integrates RStudio, SNAP, and PolSARpro software libraries to implement the same processes a user can achieve via the corresponding graphic user interfaces (GUI). The workflow includes bulk S1-SLC imagery downloads, installation and configuration of dependent software applications. Within the SNAP GUI, a base-graph was constructed, encompassing crucial processing steps such as data import, sub-swath extraction, orbit determination, calibration, speckle filtering, debursting, and terrain correction, which acts as a template for generating customized SNAP graphs for individual S1 imagery. These graphs are batch processed with R, using parallel computing to run multiple graphs simultaneously. In the subsequent PolSARpro processing phase, outputs from the SNAP processing pipeline are made interoperable with PolSARpro tools for onward post-processing. Similarly, we leverage the parallelization mechanisms of R for user specific parameter extraction, which maximizes resource utilization while maintaining computational performance. • Automated Workflow for SAR Processing: Introduces an automated, user-friendly framework combining RStudio, SNAP, and PolSARpro to process unlimited Sentinel-1 Single Look Complex (S1-SLC) images, eliminating manual interaction and catering to users with minimal programming or SAR expertise. • Customizable and Scalable Processing: Leverages SNAP's base-graph templates for essential SAR processing steps (e.g., orbit determination, calibration, speckle filtering, and terrain correction) to enable batch processing and parallel computing for efficient handling of large datasets. • Interoperability and Enhanced Performance: Integrates outputs from SNAP into PolSARpro for advanced post-processing, employing R-based parallelization to optimize resource utilization and ensure efficient user-specific parameter extraction.